Secretory pathways and multiple functions of nonstructural protein 1 in flavivirus infection - Zhang, Senzhao; He, Yu; Wu, Zhen; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Huang, Juan; et al. (Frontiers in Immunology, 2023)
The genus Flavivirus contains a wide variety of viruses that cause severe disease in humans, including dengue virus, yellow fever virus, Zika virus, West Nile virus, Japanese encephalitis virus and tick-borne encephalitis virus. Nonstructural protein 1 (NS1) is a glycoprotein that encodes a 352-amino-acid polypeptide and has a molecular weight of 46-55 kDa depending on its glycosylation status. NS1 is highly conserved among multiple flaviviruses and occurs in distinct forms, including a dimeric form within the endoplasmic reticulum, a cell-associated form on the plasma membrane, or a secreted hexameric form (sNS1) trafficked to the extracellular matrix.Intracellular dimeric NS1 interacts with other NSs to participate in viral replication and virion maturation, while extracellular sNS1 plays a critical role in immune evasion, flavivirus pathogenesis and interactions with natural vectors. In this review, we provide an overview of recent research progress on flavivirus NS1, including research on the structural details, the secretory pathways in mammalian and mosquito cells and the multiple functions in viral replication, immune evasion, pathogenesis and interaction with natural hosts, drawing together the previous data to determine the properties of this protein.